Flooding and plant growth (Academic Press, 1984)
The book discusses the cause and extent of flooding and introduces the general nature of plants responses to flooding. It addresses in depth the various effects of flooding on soil; metabolism and growth of herbaceous plants; growth and composition of communities of woody plants; physiological processes of plants, with particular emphasis on water, carbohydrate, mineral, and hormone relations; and plant diseases. The book also describes various physiological and morphological adaptations of plants to flooding with fresh and salt water